East Africa Science Workshop - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
The regional science workshop brought together participants from CGIAR, National Agricultural Research and Extension Systems (NARES), climate services and products, food security, and early warning systems to plan and develop thematic research to support climate risk management, adaptation and mitigation options in East Africa. Four thematic research groups were formed that integrates climate risk management, adaptation, mitigation and linking knowledge to action. The research groups will be working at the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) learning sites in East Africa. Photo: Tabitha Muchaba (CCAFS).